SYNTACTIC STRUCTURE OF ADJECTIVE, ADVERB AND PREPOSITIONAL PHRASES OF AWGNI - Agajie, Berhanu Asaye (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
The objective of this study is to agree to a logical inspection of syntactic structures of Awgni Adjective, Adverb and Preposition Phrases. The article attempts descriptive research design. Through purposive sampling, 12 texts were selected. Six informants (tree females and three males) were involved in group discussion to crosscheck these data. The scheme of data analysis employed in this study was x-bar syntax. Results indicated that Awgni Adjective, Adverb and Preposition Phrases were pending in a variety of head, complement, specifier and adjunct utterances. The Selections of complement, adjunct, and specifier in between phrases were to some extent syntactically similar. The study showed that syntactic structures have dominance, and precedence relationships. Finally, the study recommended a further research on some basic properties of Awgni labeling algorisms.